Non-Local Ductile Damage Formulations for Sheet Bulk Metal Forming. Issue 3 (August 2016) - Beese, Steffen; Loehnert, Stefan; Wriggers, Peter
Abstract: A ductile damage model for sheet bulk metal forming processes and its efficient and accurate treatment in the context of the Finite Element Method is presented. The damage is introduced as a non-local field to overcome pathological mesh dependency. Since standard elements tend to show volumetric locking in the bulk forming process a mixed formulation is implemented in the commercial software simufact.forming to obtain better results.